The Effect of Price, Service Quality, and Facilities on the Satisfaction of Umrah Pilgrims at PT Putra Duta Wisata, Palembang - Prameliza Alfianti; Sari Lestari Zainal Ridho; Dwi Riana (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study is entitled